The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12889-018-6113-2
|View full text |Cite
|
Sign up to set email alerts
|

Household chaos and screen media use among preschool-aged children: a cross-sectional study

Abstract: BackgroundExcess screen media use is a robust predictor of childhood obesity. Understanding how household factors may affect children’s screen use is needed to tailor effective intervention efforts. The preschool years are a critical time for obesity prevention, and while it is likely that greater household disorder influences preschool-aged children’s screen use, data on that relationship are absent. In this study, our goal was to quantify the relationships between household chaos and screen use in preschool-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 40 publications
2
53
0
5
Order By: Relevance
“…A recent review found that increased mobile connectivity distracts parents from parent-child interactions, and that distracted parents are more likely to be less responsive and sensitive to the needs of their children [133]. Further, a 2018 crosssectional study in preschool-aged children (n = 385) found that greater levels of household chaos were associated with increased total screen use in pre-schoolers and screen-use behaviours related to disrupted nighttime sleep [134]. Future research will need to determine whether screen use mediates the relationship between household chaos and outcomes, or alternatively, whether new media devices contribute to the household chaos construct itself.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found that increased mobile connectivity distracts parents from parent-child interactions, and that distracted parents are more likely to be less responsive and sensitive to the needs of their children [133]. Further, a 2018 crosssectional study in preschool-aged children (n = 385) found that greater levels of household chaos were associated with increased total screen use in pre-schoolers and screen-use behaviours related to disrupted nighttime sleep [134]. Future research will need to determine whether screen use mediates the relationship between household chaos and outcomes, or alternatively, whether new media devices contribute to the household chaos construct itself.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that screen overuse is a global phenomenon that is largely irrespective of the recession, since high ST levels are reported in several countries in which child poverty was not increased [75], including Canada [70] and Australia [71]. Nowadays, exposure to screens starts as early as infancy [76] (in high-income countries, children younger than five years exceed one hour/day of ST [77]). This can only to be expected due to the extensive availability of electronic devices-smartphones, tablets, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a 2018 cross-sectional study in preschool-aged children (n = 385) found that greater levels of household chaos were associated with increased total screen use in pre-schoolers and screen-use behaviours related to disrupted nighttime sleep (135). Future research will need to determine whether screen use mediates the relationship between household chaos and outcomes, or alternatively, whether new media devices contribute to the household chaos construct itself.…”
Section: Discussionmentioning
confidence: 99%